Production and evaluation of albino mutants of Sporothrix schenckii - Nobre, Márcia de Oliveira; Antunes, Tatiana de Ávila; Meireles, Mário Carlos Araújo; Ferreiro, Laerte (Acta Scientiae Veterinariae, 2018)
Melanin is an important factor intrinsically related to the virulence of the Sporothrix schenckii. Mutant albino conidia are usually used as inoculants for the evaluation of the properties of melanin in experimental models for the study of sporotrichosis. The goals of this study were to analyze the presence of melanin in S. schenckii conidia, and to produce and evaluate mutant albino forms of S. Schenckii conidia. Four distinct isolates were cultured in PDA, supplemented or not with triciclazole, and in YEPD. A portion of the samples was exposed to 300 ergs/mm2 of UV radiation to generate mutants albino forms. Following the incubation, cultures were analyzed, CFU were determined, and fragments were removed for the ultrastructural analysis, to be cultured once more in YEPD e BHI. Albino colonies were exposed to visible light; all S. schenckii isolates produced melanin, and survival and viability were 66% and 96% for albino conidia. Melanin granules were visible in the cell wall of pigmented conidia, but not in albino conidia. All conidia reverted to both the pigmented and the yeast forms, and albino colonies photoreactivated. All isolates analyzed in this study generated DHN melanin. Moreover, despite the exposure to UV radiation (300 ergs/mm2) being lethal to a significant portion of the colonies, the viability and conversions to the pigmented and yeast forms in surviving colonies did not appear to be affected. Also, albino colonies photoreactivated upon exposure to visible light.